Keluarga Berencana di Indonesia: Tinjauan Dampak Sosial dan Hukum Islam dalam Kajian Masail Fiqhiyah - Hani Nur Destriani; Garnisa Sundarawati; Royan Parouq Tanjil (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
This study explores the Family Planning (FP) program from social, medical, and Islamic legal perspectives through an analysis of Islamic jurisprudence. FP is defined as a measure to regulate births and the spacing between pregnancies to create healthy, prosperous, and quality families. This discussion covers a basic understanding of FP, the history of the development of the FP program in Indonesia, and various population issues that underlie its implementation. In addition, this study explains the positive impacts of the FP program on health, economic, and social development, such as reducing maternal and infant mortality rates, improving family living standards, and controlling population growth. However, it also discusses the negative impacts of the FP program, both from a health, demographic, and socio-cultural perspective. This study also pays attention to the laws related to FP in Islam, which are based on ijtihadiyah (Islamic jurisprudence) using the maqashid al-shari'ah (Islamic law). Birth control is considered valid as long as its purpose is to protect the health and well-being of the family, while permanent childbearing without a compelling reason is generally not justified. The following discussion covers contraceptive methods and devices from a medical and Islamic perspective, as well as the contribution of the government and religious organizations in educating the public about the FP program. Research findings show that the family planning program has a significant relationship with improving family welfare and community social resilience if implemented in a balanced, humane manner and in accordance with religious principles.   Keywords: Family Planning, Masail Fiqhiyah, Contraception, Islamic Law, Family Welfare, Social Resilience